Supplementary cementing materials for high performance concrete - Safiuddin, Md.; Zain, M.F.M. (BRAC University, 2010)
Supplementary cementing material is an important component of high performance concrete. In particular, the incorporation of supplementary cementing material is essential when the high strength and durability become the most desired properties of high performance concrete. The aim of this paper is to present several well known supplementary cementing materials such as silica fume, fly ash, ground granulated blast-furnace slag, rice husk ash and high reactivity metakaolin, which have been used extensively in the production of high performance concrete. This paper points at the sources, and briefly illustrates the physical properties and chemical composition of the aforementioned supplementary cementing materials. This paper also shows the major effects of the abovementioned supplementary cementing materials on fresh and hardened properties, and durability of high performance concretes.